Transmitter IQ Skew Estimation Using the Designed Training Sequence in Digital Subcarrier Multiplexing Systems - Lin, Hong; Zhang, Jing; Hu, Shaohua; Wang, Rui; Jin, Taowei; Xu, Bo; Qiu, Kun (Journal of lightwave technology, 2025)
The time delay between the in-phase (I) and quadrature (Q) components in the transmitter, i.e., the Tx IQ-skew, has been a limitation factor as the transmission data rate continuously increases. Different from single-carrier systems, Tx IQ skew leads to the aliasing of symmetric subcarriers in digital subcarrier multiplexing (DSCM) systems. In this paper, we propose a paired subcarrier estimation (PSE) method for Tx IQ skew estimation. We theoretically study the aliasing and find that both the X- and Y-polarization Tx IQ skew can be canceled in the frequency domain simultaneously when the training sequence is designed to be half of negative conjugation and the other half of conjugation on symmetric subcarrier pairs. Since the Tx IQ skew is extracted from the phase term, the estimation accuracy is dependent on the laser phase noise. To eliminate the influence of phase noise, we directly use the symmetrically paired subcarriers with conjugate sequence (CS) affected by similar phase noise. However, there still exists residual phase noise because the transmitted signal mixes with the laser phase noise. Then, we use adjacent paired subcarriers with the same sequence (SS), which shows better tolerance to laser linewidth and has lower computation complexity. Theoretical analysis and simulation results indicate that PSE methods are insensitive to the modulation format, Tx IQ amplitude and phase imbalance. Compared with the PSE-CS, the PSE-SS is robust to residual frequency offset (RFO) and laser phase noise. Finally, the PSE methods are experimentally verified in a 40-Gbaud four-subcarrier PM-16QAM DSCM signal transmission system. The estimation accuracy of PSE-CS or PSE-SS is within ±0.25 ps or 0.2 ps, respectively.